The Effect of the Use E-Commerce in the Sales Process on the Interest of Student Entrepreneurs - Putri, Septylyta Rahmita; Muzakki, Muhammad Husin Nur (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2021)
This research stems from several issues that occur in the world of the digital economy in the use of e-commerce which is currently developing. In this study, we want to know the effect of using e-commerce in the sales process on interest where the research method is directed to determine cause-and-effect relationships based on observations of the effects that occur and look for factors that cause them through the collected data. N 1 Seyegan. The sample in this study requires 100 student respondents to facilitate data processing. From the results of data processing, it was obtained an analysis that the use of e-commerce media in the growing interest in entrepreneurship at SMA N 1 Seyegan had a positive and significant effect. And seeing the sales process is able to foster interest in entrepreneurship among class XII students at SMA N 1 Seyegan has a positive and significant effect.